2017
DOI: 10.1161/jaha.117.005590
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Aortic Stiffness in Patients After ST‐Elevation Myocardial Infarction

Abstract: BackgroundHigh aortic stiffness has been shown to be a strong predictor of morbidity and mortality in the general population and several patient cohorts. However, in patients after ST‐elevation myocardial infarction, the prognostic value of high aortic stiffness is unknown so far.Methods and ResultsThis prospective observational study included 160 consecutive patients with first acute ST‐elevation myocardial infarction. Aortic pulse wave velocity (PWV) was measured 2 (interquartile range 2‐4 days) days after i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 34 publications
1
38
0
1
Order By: Relevance
“…Additionally, an increase of the arterial load due to increased aortic stiffness may also affect LV performance . Increased PWV was related with reduced coronary flow reserve in CAD patients even after successful revascularization and with elevated N‐terminal pro BNP (NT‐proBNP) post‐myocardial infarction ( Table ) . Myocardial strain imaging (LV GLS < 20%) has shown to detect subclinical dysfunction in CAD patients and represents a more sensitive method of identifying LV performance .…”
Section: Ventricular–arterial Coupling In Coronary Artery Diseasementioning
confidence: 99%
“…Additionally, an increase of the arterial load due to increased aortic stiffness may also affect LV performance . Increased PWV was related with reduced coronary flow reserve in CAD patients even after successful revascularization and with elevated N‐terminal pro BNP (NT‐proBNP) post‐myocardial infarction ( Table ) . Myocardial strain imaging (LV GLS < 20%) has shown to detect subclinical dysfunction in CAD patients and represents a more sensitive method of identifying LV performance .…”
Section: Ventricular–arterial Coupling In Coronary Artery Diseasementioning
confidence: 99%
“…Similarly, Hirsch et al described a significant relation between worse aortic stiffness and end-systolic volume index in patients after myocardial infarction [142]. A prospective observational study including 160 patients with first acute STEMI found that PWV measured two days after infarction using phase-contrast CMR is independently associated with an increased risk of major adverse cardiac and cerebrovascular events during a median follow-up of 1.2 years [137]. The assessment of aortic stiffness in addition to conventional risk factors significantly improved early risk classification in this study.…”
Section: Aortic Stiffnessmentioning
confidence: 91%
“…Although a large body of evidence has proven the prognostic implications of aortic stiffness in multiple populations, only few data exist for patients suffering a STEMI. Nevertheless, aortic stiffness has gained attention for risk prediction also in patients after STEMI [136,137]. Increased aortic stiffness as determined by aortic PWV using phase-contrast CMR has been shown to be correlated with elevated levels of natriuretic peptides and cardiac troponin in the acute and chronic stage after STEMI [138][139][140].…”
Section: Aortic Stiffnessmentioning
confidence: 99%
“…The latest results showed that the increased aortic stiffness is an independent predictor of major adverse cardiac and cerebrovascular events (MACCE) after acute STelevation myocardial infarction. The assessment of aortic stiffness in addition to classical risk factors significantly improved an early risk stratification 67 .…”
Section: Arterial Stiffness and Damage To Target Organsmentioning
confidence: 99%